The Correlation between Youth Guidance by Ustadh and Their Participantions on Wirid Remaja Activities in Surau - Adhi Sucipto; Wirdatul Aini (Universitas Negeri Padang, 2019)
The results showed that adolescent guidance by clerics in Surau Ikhsan Kuranji, Guguak Subdistrict, Lima Puluh Kota District was disseminated still low. The participation of adolescents took part in youth wirid in Surau Ikhsan Kuranji, Guguak Subdistrict, Lima Puluh Kota District was still low. There was a significant relationship between the guidance of adolescent wird by ustadz with his participation in the youth wirid in Surau Ikhsan Kuranji. Evidenced by the correlation coefficient of 0.504, with a significance test the value of t count of 3.07 is greater than t table 1.70814 at a significant level of 0.05 with dk = 25. In the results of the study it can be concluded that the higher the level of guidance of adolescents by the cleric, the higher the youth participation.Keywords: Youth Wirid, Participation